2020
DOI: 10.1093/neuonc/noaa215.560
|View full text |Cite
|
Sign up to set email alerts
|

Ncog-21. Interim Results of Three Cognitive Rehabilitation Strategies in Patients With Lower Grade Gliomas

Abstract: BACKGROUND Patients with lower grade (2 and 3) gliomas (LrGG) are living longer, but often with cognitive impairments from their tumor and treatments. However, cognitive assessments and access to cognitive rehabilitation are not a standard part of care. We present preliminary results of a pilot study investigating feasibility and efficacy of three cognitive rehabilitation strategies for stable LrGG patients – in-person manualized cognitive rehabilitation; iPad based cognitive rehabilitation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…There were also 7 (20.0%) prospective uncontrolled/pilot studies, and one (2.9%) retrospective case–control study. Three (8.6%) of the identified studies were presented in abstract form, with no full‐text study available at the time this review was conducted 4,11,14 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There were also 7 (20.0%) prospective uncontrolled/pilot studies, and one (2.9%) retrospective case–control study. Three (8.6%) of the identified studies were presented in abstract form, with no full‐text study available at the time this review was conducted 4,11,14 …”
Section: Resultsmentioning
confidence: 99%
“…Of the 21 nonpharmacological studies identified, 11 were randomised 11–15,18,19,21,37–39 and 10 were nonrandomised 16,17,20,22,40–45 . Most of the nonpharmacological studies evaluated cognitive training or rehabilitation programmes 11–18,22,38–41,43,44 . The cognitive rehabilitation was delivered through a range of modalities, including computer programs and virtual reality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations